IDENTIFIKASI FAKTOR YANG MEMPENGARUHI RETURN ON ASSETS (ROA) PERUSAHAAN PERBANKAN DI BURSA EFEK INDONESIA - Irawan (JUMANT, 2016)
This study aimed to examine the effect of CAR, PDN, LDR, PO ROA and ROAagainst the banking companies listed in Indonesia Stock Exchange eithersimultaneously or partially. The population of this study as many as 32 companiesare banking companies listed in Indonesia Stock Exchange since 2010-2014.Samples were selected using purposive sampling method amounted to 21companies. The data were processed using Least Squares Pooled analysis withrandom effects methods These results prove the CAR, PDN, LDR, PO and ROAROA simultaneously affect the banking companies listed on the Stock Exchange theperiod 2010 - 2014. Testing partially CAR, PDN, LDR, PO and ROA also affect theROA. Partial testing PO effect on ROA.